The Impact of Use of Electronic Medical Records on The Quality Of Health Services and Patient Safety: Review - Sutha, Diah Wijayanti; Christine, Christine; Masyfufah, Lilis; Faida, Eka Wilda; Wahyuni, Titin; Novianti, Siti; Syalfina, Agustin Dwi (Indonesian Journal Publisher, 2025)
Electronic Medical Records have been introduced to improve the efficiency and quality of healthcare services, as well as patient safety. This study aims to review the impact of the use of Electronic Medical Records on these aspects through a narrative review. The literature review was conducted using three databases, namely PubMed, MEDLINE, and CINAHL, with the addition of Google Scholar for wider coverage. The articles retrieved were limited to publications from January 2013 to October 2023. The implementation of Electronic Medical Records improves the efficiency of healthcare services by accelerating patient data access, reducing administrative costs, and strengthening coordination between healthcare workers. However, although the advantages of Electronic Medical Records are seen in increasing the accuracy and accessibility of medical information, there are risks to patient safety, such as data input errors and the threat of data leakage. Overall, Electronic Medical Records contribute positively to improving the quality of healthcare services, especially in chronic disease management, collaboration between medical professionals, and real-time monitoring of patient conditions, which have an impact on the continuity and effectiveness of care.